Impact of Kurdish Genocide on (Poet Muaid Tayeb) - Mohammed Omer Ibrahim; Rabeea Ismael Khalid Zebari; Hemn Krim M. Salih (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The term Anfal is the name given to a succession of attacks and genocide committed by the Ba’ath Regime against Kurdish people in the north of Iraq. Anfal literally means the spoils of war and was used to describe the military campaign of extermination and looting commanded by Saddam Hussein. The Anfal campaign takes its name Surah Al-Anfal in the Holy Quran. The Ba’athists misused what the Quran says. Hundreds of thousands of Kurdish innocent men، women، and children were killed and disappeared during the Anfal campaign. In addition، a countless number of villages were destroyed and razed to the ground. The Ba’ath Regime attempted to evict forcefully Kurdish families and wipe out them from their ancestral home، and change the demographics of Kurdistan by relocating Arabs from elsewhere in Iraq to Kurdish villages. In the 1980s، the regime’s oppression and fascism against Kurds developed and reached its peak in 1988. There is a close relationship between society and literature. Literature reflects the culture and society; its good values، and its ills، of the time in which it was set. Thus، the genocide that happened in the Badinan territory had a great influence on the intellectuals and writers and their literary works. Kurdish writers began to write novels، tales،and poems about this tragedy. Mu’ayad Tayib is one of the poets of the Badinan territory to be touched by this calamity، the Anfal.